Uso tradicional de plantas medicinales con acción diurética en el Municipio de Quemado de Güines, Cuba - Pérez Machín, Maykel (2011)
Tradicional use of medicinal plants with diuretic properties at Quemado de Güines Municipality, Cuba. Medicinal plants are highly rich in Cuba and an amount of 179 species have been reported to be used by the population for diuretic purposes, nevertheless, no experimental validation has supported this effect. This study presents the relative importance of the medicinal plant species most widely used for diuretic purposes in two communities of Quemado de Guines Municipality, Villa Clara province. The information was obtained through the application of an interview to 85 inhabitants, from which 80 were random surveys to people with a great knowledge of plants, and five to herbalists and doctors practicing natural medicine. The etnopharmacological information was registered (gathered) by means of the “Tradicional of the Medicine of the Island” (TRAMIL) methodology and the interesting species were identified by a botanist and deposited in the Herbarium of the Central University “Marta Abreu” from Villa Clara, registered in the Index Herbarium, published periodically by the International Association for Plant Taxonomy. The data was analyzed by means of the indexes of use values and significant use level after TRAMIL. From the total of 19 botanical families, 26 medicinal species were identified, and 10 plants resulted with higher significant use and higher indexes of use values. From the plants reported as diuretics, 53.8% have not been experimentally validated in Cuba, the rest of the identified species have been validated at a preclinical level in some centers in the country, but its use have not been authorized as phytochemicals by the Cuban Regulatory Agency. The documentation related to the use of medicinal plants in the studied areas reveals that the traditional knowledge continues deeply rooted in the communities, and popular wisdom is kept through the representative images of the herbalist and people with considerable knowledge about this topic.